CD4 T cell lymphoproliferative disorder associated with the primary ear epstein barr virus: Desorden linfoproliferativo de células t cd4 asociado al virus epstein barr primario de oreja - E. Beltran, Brady (2018)
Two cutaneous entities related to EBV are recognized in the 2016 World Health Organization (WHO) classification: Hydroa vacciniforme–like lymphoproliferative disorder and  Extranodal NK/T-cell lymphoma, nasal type. Rare cases of EBV primary cutaneous CD8-positive T lymphomas have been reported. These lymphoid proliferations do not fit into any of the two classical EBV-related lymphomas .We report a unique case of an  Epstein-Barr Virus-associated Primary Cutaneous –CD4-positive T-Cell Lymphoproliferative Disorder  affecting the bilateral ears  with indolent outcome and subsequent relapse on the tongue and trunk skin. Key words: EBV; CD4; lymphoma; Skin; Ear. (source: MeSH NLM)   DOI: 10.25176/RFMH.v18.n2.1289